TRADISI BAKAR TONGKANG DI KOTA BAGANSIAPIAPI KECAMATAN BANGKO KABUPATEN ROKAN HILIR, RIAU - Redah Jeiyusman; Teguh Widodo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Riau is a province that has a variety of cultures, and one of them is the bakar tongkang tradition in the city of Bagansiapiapi, Bangko District, Rokan Hilir Regency. This tradition has become a hereditary heritage from ethnic Chinese in the city of Bagansiapiapi so this makes this tradition held every year. The aims of this research are (1). To find out the government's role in the success of the bakar tongkang tradition in the city of Bagansiapiapi. (2). To find out the ritual procession carried out by the government in the success of the bakar tongkang tradition in the city of Bagansiapiapi. This study used a descriptive qualitative method with a purposive sampling technique, in this study there were 6 informants from the community in the city of Bagansiapiapi. The results of this study are that the government's role is to maintain order and security during the event, regardless of the form of participation that is carried out, namely participation labor and financial participation, while for the research results from the second formulation, ritual processions carried out by the community, namely praying, parading the barge and seeing the burning of the barge Keywords: Roles, Rituals, Government